2009
DOI: 10.1021/ic900784t
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses, Crystal and Electronic Structures, and Physical Properties of Two Quaternary Chalcogenides: La4FeSb2Q10(Q = S, Se)

Abstract: Two new quaternary chalcogenides, La(4)FeSb(2)S(10) and La(4)FeSb(2)Se(10), have been synthesized from the stoichiometric mixture of elements by solid-state reactions at 1100 degrees C. The compounds crystallize in the orthorhombic space group Pbcm with a = 15.066(4) A, b = 7.590(2) A, c = 13.341(4) A, and Z = 4 and a = 15.596(5) A, b = 7.869(2) A, c = 13.960(4) A, and Z = 4, respectively. These structures represent an unique three-dimensional network, in which SbQ(3) trigonal pyramids (Sb-S < 2.60 A, Sb-Se < … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(22 citation statements)
references
References 39 publications
4
18
0
Order By: Relevance
“…In contrast, the other two crystallographically independent La sites, La3 and La4, are located in approximately square antiprismatic environments with La–S bond lengths between 2.89 and 3.26 Å. All these La–S distances are reasonable, as are the ones found in the La 6 Si 2 MgS 14 (2.88–3.11 Å),21 La 7 Sb 9 S 24 17 (2.79–3.54 Å), and La 4 FeSb 2 S 10 (2.90–3.34 Å) 20…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…In contrast, the other two crystallographically independent La sites, La3 and La4, are located in approximately square antiprismatic environments with La–S bond lengths between 2.89 and 3.26 Å. All these La–S distances are reasonable, as are the ones found in the La 6 Si 2 MgS 14 (2.88–3.11 Å),21 La 7 Sb 9 S 24 17 (2.79–3.54 Å), and La 4 FeSb 2 S 10 (2.90–3.34 Å) 20…”
Section: Resultssupporting
confidence: 76%
“…For comparison, the compound La 7 Sb 9 S 24 is characterized by chains of severely distorted SbS 5 square pyramids, which are interconnected through four‐coordinate Sb atoms to form 1D ribbons separated by La cations 17. The structure of La 4 FeSb 2 S 10 contains SbS 3 trigonal pyramids (Sb–S < 2.6 Å), which are connected through a relatively weak Sb–S bond (Sb–S ≈ 2.9 Å) in a novel teeter‐totter (SbS 4 ) n chain motif 20. It is obvious that the ratio La/Sb affects the dimensions of the Sb/S framework.…”
Section: Resultsmentioning
confidence: 99%
“…The maximum point in the valence band and the minimum point in conduction band are both located at the Γ point. Thus, La2CuBiS5 is a semiconductor with a direct band gap of 1.31 eV, which is consistent with the value 1.30 eV measured by optical diffuse reflection spectroscopy [28]. We plotted the band structure in the energy window −1.0-2.0 eV, because the thermoelectric properties were mainly determined by the energy bands near the Fermi level.…”
Section: Electronic Structuresupporting
confidence: 85%
“…On the one hand, Ag(I) ion possesses flexible coordination modes and coordination numbers from two to eight, so structures of AgÀLn polymers exhibit novel and diverse. [25][26][27][28][29] For example, Yi-Fan Kang et al report one AgÀEr polymer using 4,5-imidazoledicarboxylic acid as ligand with 1D pseudo-nanotube architectures, [30] a series of 2D cellular LnÀAg coordination polymers are reported by Xiao-Qing Zhao et al, [31] LnÀAg polymers with 3D network are reported by Zhi-Hui Liu et al, [32] one EuÀAg coordination polymer with racemic-spiral structure is reported by Yue-Peng Cai et al, [33] and so on. On the other hand, d-block chromophores formed by Ag(I) ion and organic ligands can reduce the energy of organic ligand's triplet state, which is conducive to d!f energy transfer and enhance the luminescence of Ln(III) polymers.…”
Section: Introductionmentioning
confidence: 99%